Robert J. Donia and John V. A. Fine Jr., Bosnia and Hercegovina: A Tradition Betrayed, and Robert J. Donia, Sarajevo: A Biography - Svirčević, Miroslav (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Robert J. Donia and John V. A. Fine, Jr., Bosnia and Hercegovina. A Tradition Betrayed, New York: Columbia University Press, 1994, pp. 318. Robert J. Donia, Sarajevo: A Biography. Ann Arbor: University of Michigan Press, 2006, pp. 435.